Arsenic profiling of groundwater in river cities of Lahore, Hyderabad and Muzaffarabad in Pakistan. Issue 9 (6th October 2022) - Din, Salah Ud; Hussain, Babar; Raja, Sobia; Khaqan, Urooj; Haq, Sirajul; Waris, Muhammad
Abstract: Arsenic contamination in Pakistan has never been considered a serious problem. The present study therefore is based on a more detailed screening of arsenic in groundwater samples of Hyderabad and Lahore in addition to Muzaffarabad where no sufficient data on arsenic screening has been reported until now. A total of 160 samples were collected from various sites of Hyderabad, Lahore and Muzaffarabad and analyzed for arsenic by using hydride generation system. The order of percentage of samples having arsenic concentration greater than the WHO limit (>10 µg L −1 ) in the three cities was as follows: Lahore > Hyderabad > Muzaffarabad with Lahore city having arsenic concentration even greater than 50 µg L −1 in water samples of Nishtar colony, Dograiy Kallan and Yuhanabad. The mean average daily dose (ADD), hazard quotient (HQ) and carcinogenic risk (CR) values for Lahore, Hyderabad and Muzaffarabad were also found in the order Lahore > Hyderabad > Muzaffarabad. The health risk for children calculated in this investigation was found to be more than the adults. In current study, the physical parameters such as pH, total dissolved solids (TDS), electrical conductivity (EC) and chemical parameters like Mg +2, Ca +2, CO2, HCO3 −1, and CO3 −2 were also investigated. The current investigation shows the city of Lahore to be the most effected by arsenic contamination followed by Hyderabad whereas Muzaffarabad is the least effected.